Vitamin C and Cardiovascular Disease: An Update - Marco B. Morelli; Jessica Gambardella; Vanessa Castellanos; Valentina Trimarco; Gaetano Santulli (MDPI AG, 2020)
The potential beneficial effects of the antioxidant properties of vitamin C have been investigated in a number of pathological conditions. In this review, we assess both clinical and preclinical studies evaluating the role of vitamin C in cardiac and vascular disorders, including coronary heart disease, heart failure, hypertension, and cerebrovascular diseases. Pitfalls and controversies in investigations on vitamin C and cardiovascular disorders are also discussed.